Discurso do desenvolvimento sustentável: a polêmica relação entre preservação ambiental e desenvolvimento econômico - SERRÃO, Glaciane Felipe (Universidade Federal do Pará, 2014)
This research has the objective to investigate the polemics founder of the discourse of sustainable development. It is to note how the positioning of sustainable development constituted his identity from the relationships they have with their interdiscursive Other discursive space, namely the placement and positioning developmental environmentalist. We seek to examine the simulacra that the positioning of sustainable development, in the position of speech-agent builds its more discursive, in the position of speech patient from interincomprehension orderly process and, concomitantly, the image he seeks to establish Even you. The corpus of this research consists of texts that circulate in two media outlets specializing in environmental issues: the Institute website Akatu and Portal Environment. The approach to this corpus will be based on theoretical and methodological perspective of French Discourse Analysis, mainly the concepts of polemics as interincomprehension and interdiscourse proposed by Maingueneau (2005).